1 2 2

:

  1. #1

    Jul 2012
    5,302

    :-
    14
    12 7
    :-
    1-
    2-
    :-
    1) = ^2
    = ( 14 )^2 12 ^3
    = ^2
    = ( 7 )^2 12 ^3
    = / = (14)^2 12 / (7 )^2 12
    = 4 / = 4:
    2)
    = + + 2 [ - ]
    = 4 14 12 + 2 ( 7) 12 + 2 [( 14)^2 - ( 7)^2 ]
    = 1284 ^2


    :-
    28 11
    .
    :-
    = ^2
    = 22/ 7 / 11 11 28
    = 22 11 11 4 = 10648 ^3

    = 10648 ^3
    = = 10648 = 22
    = 6
    = 22 22 6 = 2904 ^2


    :-
    38 5
    912 ^2 .
    :-

    = ...............( )
    = = 912 38 = 24

    ( ) = 12
    5

    = ( ( 12)^2 + ( 5)^2 = 169 = 13
    = 2 + 2 ^2
    = 2 ( 13 ) ( 38 ) + 2 ( 13)^2 = 1326 ^2


    :-
    44 25

    :-
    = ^2

    = 2
    44 = 2 22 / 7
    = 44 7 / 2 22
    = 7
    = ^2
    = 22/ 7 7 7 25
    = 22 7 25 = 154 25 = 3850 ^3


    :-
    52 8 :

    832
    :-
    = ^2
    = 2
    52 = 2 22 4 / 7
    = 52 7 / 2 4 22
    = 26 7 / 4 22
    = 13 7 / 2 22 ............... = 13 / 2
    = ^2
    = 4 4 13 / 2
    = 2 4 13 = 8 13 = 104 ^3
    = /
    = 832 / 104 = 8 / ^3















  2. #2
      Eiman
    Jul 2011
    -
    14,750

    :

    .......

: 1 (0 1 )